Macro‐ and micro‐sedimentology of a modern melt‐out till – Matanuska Glacier, Alaska, USA. (30th December 2015) - Larson, Grahame J.; Menzies, John; Lawson, Daniel E.; Evenson, Edward B.; Hopkins, Nathan R.
Abstract : The macro‐ and micro‐sedimentology of a supraglacial melt‐out till forming at the Matanuska Glacier was examined in relationship to the properties of the stratified basal zone ice and debris from which it is originating. In situ melting of the basal ice has produced a laminated to bedded diamicton consisting mainly of silt. Macroscopic properties include: discontinuous laminae and beds; lenses of sand, silt aggregates and open‐work gravel; deformed and elongate clasts of clay; widely dispersed pebbles and cobbles, those that are prolate usually with their long axes subparallel to parallel to the bedding. Evidence for deformation is absent except for localized bending of beds over or under rock clasts. Microscopic properties are a unique element of this work and include: discontinuous lineations; silt to granule size laminae; prolate coarse sand and rock fragments commonly with their long axis subparallel to bedding; subangular to subrounded irregular shaped clay clasts often appearing as bands; sorted and unsorted silt to granule size horizons, sometimes disrupted by pore‐water pathways. Limited deformation occurs around rock clasts and thicker parts of lamina. This study shows that in situ melting of debris‐rich basal ice can produce a laminated and bedded diamicton that inherits and thereby preserves stratified basal ice properties. Production and preservation of supraglacial melt‐out till require in situ melting of a stagnant, debris‐rich basal ice source with a low relief surface that becomes buried by a thick, stable, insulating cover of ice‐marginal sediment. Also required are a slow melt rate and adequate drainage to minimize pore‐water pressures in the till and overlying sediment cover to maintain stability and uninterrupted deposition. Many modern and ancient hummocky moraines down glacier of subglacial overdeepenings probably meet these process criteria and their common occurrence suggests that both modern and pre‐modern supraglacial melt‐out tills may be more common than previously thought.